2015
DOI: 10.5603/cj.a2015.0023
|View full text |Cite
|
Sign up to set email alerts
|

Significance of ST-segment deviation in patients with acute pulmonary embolism and negative T waves

Abstract: Background: Common electrocardiogram (ECG) manifestations in acute pulmonary embolism (APE) include ST-segment deviation (STDV) along with negative T-waves (NTW). STDV could occur in 3 typical ischemic patterns: (i) the left ventricular (LV) subendocardial ischemic pattern; (ii) the right ventricular (RV) transmural ischemic pattern; and (iii) the LV intensification of therapy, and death compared to patients without STDV (p = 0.001 for each variable). The majority (89%) of the patients with STDV presented with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…Twenty‐one studies (4105 patients) had clinical deterioration as an outcome . Statistically significant features from the meta‐analysis included sinus tachycardia, S1Q3T3, TWI, complete RBBB, any RBBB, ST‐segment depression in V 4 through V 6 , STE‐aVR, STE‐V 1 , STE‐III, Qr‐V 1 , and AF at admission (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐one studies (4105 patients) had clinical deterioration as an outcome . Statistically significant features from the meta‐analysis included sinus tachycardia, S1Q3T3, TWI, complete RBBB, any RBBB, ST‐segment depression in V 4 through V 6 , STE‐aVR, STE‐V 1 , STE‐III, Qr‐V 1 , and AF at admission (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Adjusted total mortality reported by these studies did not impact the association, but had an I 2 of 54% (Table ). Zhan et al., investigated 30‐day mortality, but did not find a significant association for any of their three separate criteria for abnormal QRS morphology in V 1 (Zhan et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Zhan et al., showed that abnormal QRS morphology in V 1 was present in 20% of patients at baseline, and the prevalence increased to 95% in those patients during hemodynamic instability ( p = .001) (Zhan et al., ). Zhan et al., investigated the association with the need to intensify therapy, including cardiac arrest, need for inotropic support, mechanical ventilation for respiratory support, or thrombolysis or surgical thrombectomy (Zhan et al., ). They did not find a significant association for any of their three separate criteria for abnormal QRS morphology in V 1 (Zhan et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations